THE NECESSITY OF PRESERVING RELIGION - Bayinat Basha Al Bajali, Abul Firdaus (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
This research came on an important topic, the importance of which was agreed upon by all nations, regardless of their sects, as guidance and as a reminder to the nation on its great impact on preserving these necessities, and on understanding their purposes from the Creator to attain happiness in this world and the hereafter, and I made it into the following issues:The importance of religionPictures of preserving religionIn it I dealt with the definition of objectives in language and terminology and among contemporary scholars, then I turned to talk about the emergence and development of the science of objectives since the time of the Messenger, may God’s prayers and peace be upon him, to the scholar Ibn Ashour and Allal Al-Fassi, passing through Imam Al-Juwayni, Al-Ghazali, Al-Shatibi and other imams of the objectives.This research has been devoted to clarifying the first of the five necessities (preserving religion), which is one of the most important purposes of Sharia, and I have simplified it in detail.And for this, I extrapolated the verses in which the conditions of earning are mentioned in the Holy Qur’an, using the inductive method, and then I interpreted the verses and explained hadiths, criticism and deduction using the analytical method.